Particular Characters in Heritage Tourism to Attract Visitors: A comparative study in Sumatra, Indonesia - Nurlisa, Ginting; Nurinayat Vinky, Rahman; Achmad Delianur, Nasution; Julaihi, Wahid (AMER ABRA by e-International Publishing House, Ltd., UK., 2021)
Sumatra is one of the provinces in Indonesia that has great heritage tourism potential. The existence of attractive cultural buildings and traditional transportation is the particular character of heritage tourism. Heritage tourism significant benefits the economy and quality of life by showing the particular character of local people and culture. This study was conducted to compare particular characters with similar heritage tourism in Sumatra using a concurrent mixed-method. This study indicates monumental historical buildings and traditional transportation with particular characters significantly attract tourists and influence their intention to visit and revisit.